Pemberdayaan UMKM Angkringan Milenial melalui Legalitas Usaha di Desa Cikuya, Kecamatan Banjarharjo, Kabupaten Brebes - Adik Candra; Hendri Sucipto; Dwi Harini; Nasiruddin Nasiruddin; Roni Roni; Alim Mutaqin (Pusat Riset dan Inovasi Nasional, 2022)
Micro, Small and Medium Enterprises (MSMEs) are a form of small business whose existence plays a very important role in empowering the community to have independence in the economic field. MSMEs that are used as partners in this community service activity are people who are members of industrial houses in Cikuya Village, Brebes Regency. The purpose of this service is to describe the empowerment process through MSMEs and to describe the factors that encourage and hinder community empowerment in the legality of business in micro, small and medium enterprises. By having business legality, business actors are expected to be able to compete in the free market era. The method used in this service activity is carried out in the form of counseling, training and assistance in managing business legality. Data collection techniques used through interviews, observations, and documentation. The results of this service show that the community empowerment process runs gradually, namely preparation, assessment, implementation, evaluation and termination. The driving factor for community empowerment is the government's support in the form of training programs and resource persons, and the high motivation of the community to make good use of local potential. Meanwhile, the inhibiting factor is science and insight into online marketing techniques that have not been widely developed and lack assistance from related parties in managing business legaility